PARENTS’ ROLE IN MOTIVATING THEIR CHILDREN TO STUDY ENGLISH DURING THE COVID PANDEMIC 19 - Khudriyah Khudriyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
This research discusses about parents role to motivate their children to stud English during Corona Virus pandemic. This study is case study in MTs arrohman and MTs al Urwatul Wutsqo Jombang. Using qualitative descriptive, interview and observation as instrument. The data collected by Miles & Huberman model. This study resulted that parents’ role in motivating their children to learn English during pandemic are as educator, motivator, facilitator, and being good models for their children. To do that, they faced some problem, and overcome them by advising patiently, working cooperatively with other parents to prohibit their children from playing while studying, and devide time well. The children motivation to study English depended on the way their parents motivated.